Discover nature in the garden : things to know and things to do - Conrad, Jim. (Mechanicsburg, PA : Stackpole Books, 1996)
Looks at different aspects of the garden environment, investigating how plants are put together and how they work, observing the creatures that live in gardens and flower beds and discussing how nature's serious components interrelate.
Includes bibliographical references (p. 225-227).
Booklist.
Library Journal.
Wilson's Senior High School.
Young Adult
Keywords: Garden ecology; Gardening; Nature study; Garden ecology; Gardening; Nature study